KOMPETENSI KEPRIBADIAN GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK PESERTA DIDIK - Sa'adah, Siti (UNISAN JURNAL, 2023)
The personality development of students in schools, especially in moral development, is an important theme and gets the attention of all education practitioners. Based on the background of the problem, So the researcher wants to know "Personality Competence of Aqidah Akhlaq Teachers in Fostering the Morals of Students at Madrasah Tsnawiyah Regency for the Academic Year 2022/2023". The main objectives of this study are 1) To find out how the personality competence of aqidah akhlaq teachers at Madrasah Tsanawiyah , 2) To find out how the moral development of students at Madrasah Tsanawiyah . The method used in this study is a qualitative research by taking the background of Madrasah Tsanawiyah . The data collection technique used is the method of observation (observation), interviews (interviews), and documentation. Data analysis was carried out through several stages, namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the personality competence of the aqidah akhlaq teacher at Madrasah Tsanawiyah is known as follows: 1). In the aspect of faith and piety, they have behaved that reflect piety. 2). Noble morals act according to religious norms. 3). Wise and wise who shows openness in thinking and acting. 4). Authoritative has a behavior that has a positive effect on students, has a respected behavior. 5). Stable, proud as a teacher with indications of having consistency in acting according to norms. and work independently in a professional manner.